Association of abruptio placenta in patient with pre-eclampsia with severe features and without severe features - Nagaraj, Rakshith; Ramakrishnappa, Hemalatha C.; Chandrashekhar, Anusha B.; L. Iyengar, Swathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Placental abruption is responsible for increased risk of maternal and fetal morbidity and mortality worldwide. Studies specific to placental abruption in pregnancy-induced hypertension (PIH) are still lacking. This study is designed to focus on collecting data on placental abruption and to objectively determine its impact on the outcome of pregnancy complicated with PIH in terms of improving fetal and maternal morbidity and mortality. Methods: This was retrospective observational study conducted at Cheluvamba Hospital, Mysore Medical College and Research Institute (MMCRI), Mysore, in the department of obstetrics and gynaecology. All pregnant women with diagnosis of abruptio placenta over 28 weeks and with PIH between January 2022 to August 2023 were included. Data was collected from medical records department and results were analysed. Results: During the study period there were total of 14027 deliveries. Of this 63 (0.44%) occurred in patients with placental abruption with PIH. Mean age group was 24.57 years; majority were multigravida (58.46%) Majority were preterm (77.77%). 61.90% had pre-eclampsia with severe features. Mean systolic blood pressure (SBP) was 151.90 mmHg, diastolic blood pressure (DBP) was 98.73 mmHg. 65.08% delivered by caesarean section. 47.61% was the perinatal mortality, perinatal asphyxia was 45.71%, prematurity was 65.71%, low birth weight was 84.12%. 71.42% was the neonatal intensive care unit (NICU) admission rate. Maternal complications seen was postpartum haemorrhage (PPH) (31.74%), requiring blood and blood products transfusion (63.49%), coagulopathy (14.28%), shock (12.69%). 4 women developed severe features of pre-eclampsia in postpartum period, 2 of them needed MgSO4. 58.73% had requirement of antihypertensives in postpartum period. Conclusions: Abruption is one of the obstetric emergencies. In our study severe adverse maternal and perinatal outcomes were more pronounced in pre-eclampsia with severe features and it needs an individual and intense surveillance and management to have better maternal and perinatal outcome.